1989
DOI: 10.1177/088506668900400306
|View full text |Cite
|
Sign up to set email alerts
|

Prevention, Care, and Treatment of Pressure (Decubitus) Ulcers in Intensive Care Unit Patients

Abstract: Pressure (decubitus) ulcers occur in approximately 4% of hospitalized patients. Patients in intensive care units are particularly at risk because they are relatively im mobile. Prolonged pressure, shearing forces, friction, and moisture are all etiological factors. Pressure ulcers may be complicated by infection and, rarely, carcinoma. Prevention depends on excellent nursing care that con centrates on meticulous skin care and relief of pressure. Once a pressure ulcer occurs, alleviation of local pres sure, mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 33 publications
0
28
0
Order By: Relevance
“…They are believed to occur from combination of extrinsic forces such as pressure, shear, and friction and intrinsic factors such as age, malnourishment, and consciousness level that influence a person's tissue tolerance [5, 6]. Previous studies have identified the following factors as increasing the likelihood of developing a pressure ulcer: immobility, admission to the ICU, malnutrition, incontinence, hypoalbuminemia, spinal cord injury, stroke, reduced level of consciousness, fractures and/or major orthopedic procedure, advanced age, trauma, decreased perfusion, poor wound healing, inadequate nursing care, and chronic illness [7–10]. …”
Section: Introductionmentioning
confidence: 99%
“…They are believed to occur from combination of extrinsic forces such as pressure, shear, and friction and intrinsic factors such as age, malnourishment, and consciousness level that influence a person's tissue tolerance [5, 6]. Previous studies have identified the following factors as increasing the likelihood of developing a pressure ulcer: immobility, admission to the ICU, malnutrition, incontinence, hypoalbuminemia, spinal cord injury, stroke, reduced level of consciousness, fractures and/or major orthopedic procedure, advanced age, trauma, decreased perfusion, poor wound healing, inadequate nursing care, and chronic illness [7–10]. …”
Section: Introductionmentioning
confidence: 99%
“…The study group received topical sildenafil ointment daily and the control group received daily topical application of placebo ointment. All patients received standard care for PrU including reduction of local pressure on damaged skin, maintaining the clean base of ulcer and correcting patients' nutritional conditions and other medical factors such as blood sugar level that might interfere with the healing process .…”
Section: Methodsmentioning
confidence: 99%
“…Inclusion criteria 1 were patients > 65 years old with pressure ulcers at stage II or III of the National Pressure Ulcer Advisory Panel (those with stage IV were treated by the plastic surgery service). Exclusion criteria 1 were prior surgical treatment of pressure ulcers, 2 septic state, 3 mechanical breathing support, 4 state of coma or brain death, 5 ingestion of steroids, and abandonment of the patient by their family 6 . Additionally, elimination criteria were errors in the clg‐pvp intradermal injection dose 1 and rejection of continuing the treatment by the patient 2…”
Section: Methodsmentioning
confidence: 99%